2001
DOI: 10.1097/00000539-200107000-00003
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Vasopressin on Systemic Hemodynamics in Catecholamine-Resistant Septic and Postcardiotomy Shock: A Retrospective Analysis

Abstract: In this retrospective analysis, the influence of a continuous infusion of an endogenous hormone (arginine vasopressin) on systemic hemodynamics and laboratory variables was assessed in patients with vasodilatory shock unresponsive to conventional therapy. Arginine vasopressin was effective in reversing systemic hypotension. However, adverse effects on gastrointestinal perfusion and coagulation cannot be excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
127
2
9

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(150 citation statements)
references
References 21 publications
12
127
2
9
Order By: Relevance
“…We did not observe evidence of myocardial ischemia in any of the patients during the 24 hour study period, which is in accordance with other studies [12]. Ischaemic skin lesions have been reported in patients receiving vasopressin treatment [13,14].…”
Section: Discussionsupporting
confidence: 92%
“…We did not observe evidence of myocardial ischemia in any of the patients during the 24 hour study period, which is in accordance with other studies [12]. Ischaemic skin lesions have been reported in patients receiving vasopressin treatment [13,14].…”
Section: Discussionsupporting
confidence: 92%
“…Comparisons of the hemodynamic effects of angiotensin II with vasopressin derivatives are not possible based on these data. Previous studies, however, reported consistent increases of both systemic vascular resistance and arterial blood pressure during arginine vasopressin infusion in patients with advanced vasodilatory shock and norepinephrine requirements >0.5 µg/kg/min (6).…”
mentioning
confidence: 78%
“…22,23 Reductions in systemic blood pressure are known and may require concurrent administration of vasopressors. 23 However, the importance of maintaining systemic blood pressure and, subsequently, right coronary pressure and flow in the face of RV dysfunction may not be as well appreciated.…”
Section: Managing Rv Failurementioning
confidence: 99%
“…9 Although the use of vasopressors can be beneficial, its prolonged administration can also contribute to systemic organ failure. 22 Specifically, prolonged administration (more than 48 h) of vasopressin has been linked to hepatic failure, renal failure, and thrombocytopenia. 22 For the case presented, systemic organ dysfunction seemed to be related, at least in part, to prolonged administration of vasopressin and not failure of the RV to eject.…”
Section: Managing Rv Failurementioning
confidence: 99%
See 1 more Smart Citation